Analisis Kesalahan Ejaan Bahasa Indonesia dalam Artikel Ilmiah Mahasiswa - Helda, Trisna; Elvia, Dona; Yulianti DN, Upit; Kamcani, Ferdian (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2023)
Writing scientific articles for students is not as easy as writing free articles. The most basic thing in writing scientific articles is not only grammar but also the systematics of writing. A writer should pay attention to good and correct writing in accordance with Enhanced Spelling (EYD). This study aims to find out Indonesian spelling errors in scientific articles for students of the Indonesian Language and Literature Education Study Program Class of 2019 at PGRI University, West Sumatra. This is qualitative research with a descriptive method. The data collection technique used is a documentary study technique. The data were obtained from document analysis, namely Indonesian spelling errors in student scientific articles. The use of documentary study techniques in this study was assisted by instruments in the form of data recording cards, data reduction, data presentation, and drawing conclusions with verification. The data was analyzed by noting Indonesian spelling errors and selecting each incoming piece of data from the documentation, then processing and focusing all the raw data to make it more meaningful. The results showed that these errors were found in (a) the use of italics and capital letters, and (b) writing errors. (c) errors in the use of punctuation marks (d) errors in writing absorption elements; (e) errors in the systematics of writing scientific articles in the form of errors in writing the title; (f) mistakes in writing abstracts and keywords (g) mistakes in writing the introductory part (h). mistakes in writing the main part (results and discussion) (i). mistakes in writing the closing part (conclusion) (j). Error in writing the reference list.